Intrinsic Control of Surface Immune and Epithelial Homeostasis by Tissue-Resident Gut Stromal Cells - Kurashima, Yosuke; Tokuhara, Daisuke; Kamioka, Mariko; Inagaki, Yutaka; Kiyono, Hiroshi (Frontiers in Immunology, 2019)
The epithelial layer creates a chemical and physical barrier at the forefront of intestinal mucosa, and immune cells beneath the surface epithelium are poised to react to extrinsic factors, to maintain tissue homeostasis. Importantly, the nexus of epithelial–immune responses at mucosal surfaces is dexterously modulated by intrinsic stromal–mesenchymal cells. First, organogenesis of lymphoid tissues, including Peyer’s patches, requires dynamic interplay between lymphoid cells and stromal cells, which have become known as “lymphoid organizers.” Second, correct spatiotemporal interaction between these cell populations is essential to generate the infrastructure for gut immune responses. Moreover, immune cells at the intestinal barrier are functionally modulated by stromal cells; one such example is the stromal cell–mediated differentiation of innate immune cells, including innate lymphoid cells and mast cells. Ultimately, mucosal stromal cells orchestrate the destinations of epithelial and immune cells to maintain intestinal immune homeostasis.